Diversity, Equity, and Inclusion For Dummies (For Dummies, 2022)
Strengthen your company culture through inclusive and equitable policies and practices The global workforce and marketplace will continue to undergo dramatic demographic shifts--redefining the workplace, the workers, and how work gets done. Organizations that want to attract and retain the best talent and to capitalize on the full breath of their perspectives and experiences must first reflect our society as a whole, and secondly, must create the right kind of work environment where ALL talent can thrive. That means valuing diversity, creating more equitable policies and practices, and fostering a welcoming and inclusive culture. In Diversity, Equity & Inclusion For Dummies, global workforce expert, and three-time Chief Diversity and Inclusion Officer Dr. Shirley Davis unveils her extensive collection of real-world experiences, stories, case studies, checklists, assessments, tips, and strategies that will give you a deeper understanding of the business impact of DEI and how your role as a leader can contribute to your company's long term success. You'll learn: The fundamentals of DEI and how it drives business performance and impact How to conduct comprehensive DEI organizational assessments to identify systemic and institutional inequities Tactics and strategies for having necessary but difficult conversations, and how to make them impactful Skills and competencies that every leader needs in order to effectively lead the new generation of workers How to operationalize DEI across your organization, measure its impact, and sustain it long term Diversity, Equity & Inclusion For Dummies is a must-read guide for any leader at any level who wants to ready themselves for the workplace of the future and reap the benefits of a full spectrum diverse ideas, backgrounds, and experiences. It also belongs on the reading lists of human resources and DEI professionals actively seeking to go broader, deeper, and have greater impact in their DEI work.